2020
DOI: 10.1002/pmrj.12382
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physical Therapy and Physician Pathways for Employees with Recent Onset Musculoskeletal Pain: A Randomized Controlled Trial

Abstract: Background Life expectancy of the U.S. population will continue to rise, increasing the workforce demands in the treatment of musculoskeletal pathologies. With a declining primary care physician workforce, physical therapists (PT) may be in a unique situation to help absorb this demand. Objective Our primary objective was to compare physical function between two primary care groups, a “physical therapy‐led pathway” versus “physician‐led pathway” in the management of recent‐onset musculoskeletal pain at 1‐month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Of the 63 articles screened for full text, a total of 28 articles were included in the review. The 28 included studies were published from 1999 to 2022 [ 9 , 16 , 17 , 18 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The following study designs were identified: 10 RCTs, 9 prospective longitudinal cohort studies, 4 case control studies, 3 retrospective observational studies, and 2 prospective observational studies [ 9 , 16 , 17 , 18 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 63 articles screened for full text, a total of 28 articles were included in the review. The 28 included studies were published from 1999 to 2022 [ 9 , 16 , 17 , 18 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The following study designs were identified: 10 RCTs, 9 prospective longitudinal cohort studies, 4 case control studies, 3 retrospective observational studies, and 2 prospective observational studies [ 9 , 16 , 17 , 18 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies [ 16 , 19 , 26 , 29 , 39 , 40 , 41 ] did not include a control. Interventions for the control group were delivered by a physician in eight studies [ 27 , 28 , 31 , 34 , 43 , 45 , 46 , 48 ]; by a general practitioner in eight studies [ 9 , 32 , 35 , 36 , 37 , 38 , 44 , 47 ], and by an orthopedic physician in five studies [ 17 , 18 , 30 , 33 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations